HUBUNGAN STATUS GIZI TERHADAP PERKEMBANGAN KOGNITIF ANAK PRASEKOLAH - Dameria " Sonata; Juniar " Ernawaty; Febriana " Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aimed to find the relation of nutritional status to cognitive development of preschool children at Pertiwi Kindergaten Pekanbaru. This study design was correlational descriptive using cross sectional design. The samples were choosen using stratified random sampling technique. The number of samples were 100 respondent of students in Pertiwi Kindergaten Pekanbaru. The data were collected by giving questionairre to the students. The analyses used were univariate analysis to find the frequency distribution and bivariate analysis using chi-square test.  The result of the study showed that from 100 respondents, those that had a low nutrional status are 25 students (75%) and good nutritional status 75 students (75%).  While the students with less cognitive development were 12 students (12 %) and good cognitive development were 88 students (88%). This study indicated that there is no relation between nutritional status and cognitive development of preschool student (p value= 0,169, p < 0,05). This study recommend to identify other factors that can increase the nutritional status and influence the cognitive development in children. Keywords : Cognitive Development, Nutritional Status, Preschool Children References : 42 (2005-2015)